Polydrug use with opioid involvement: Results from a national sample of U.S. civilians aged 12 years or older - Kele Ding; Saroj Bista; Trisha Welter; Krista K. Wheeler; Gary A. Smith; Jingzhen Yang (PLoS ONE, 2026)
This study examined the prevalence and patterns of polydrug use among a national sample of civilians aged 12 years or older, with a focus on polydrug use involving opioids, assessing the influence of the first drug used on these behaviors. Using 2020 National Survey on Drug Use and Health (NSDUH) data, five mutually exclusive drug groups were identified in a hierarchical order: opioid use, stimulant or psychoactive drug use, non-opioid prescription drug misuse, marijuana use, and legal substance use. Polydrug use was defined as the use of drugs from two or more groups. Among 32,893 participants, the prevalence of past-month polydrug use (but not within the past year) was 11.4%, while past-year use (but not past month) was 2.8%. Among participants who used opioids in the past month, 89.2% engaged in polydrug use; among those with past-year opioid use, 48.0% engaged in polydrug use. Of those engaging in past-month and past-year polydrug use, 7.0% and 32.5% used opioids, respectively. Participants who identified as female and Hispanic had lower odds of polydrug use than their respective counterparts. Respondents who initiated drug use with opioids had over five times higher odds of past-month (odds ratio [OR] = 5.45, 95% confidence interval (CI): 2.61–11.37) and past-year ( OR = 5.58, 95% CI: 2.76–11.29) polydrug use than those whose first use involved legal substance use. Their odds of opioid-involved polydrug use were 15.56 times higher for past-month use ( 95% CI: 4.92–49.18) and 54.66 times higher for past-year use ( 95% CI: 23.80–125.55). While opioid use in the general population is low, it is highly prevalent among those engaging in polydrug use with opioids as their first drug. Efforts to prevent polydrug use should prioritize those who identify as male or whose first drug was opioids, using targeted education, harm reduction, and other prevention strategies.